Reflections on Reflection (Existential Analysis: Journal of the Society for Existential Analysis, 2002)
This paper presents some thoughts on what it means to reflect on ones own experience from a phenomenological point of view. Reflecting on experience is a human quality that presents us with certain dilemmas about the nature of reality and our substance as beings. These general points are then related to the specific therapeutic tasks of talking and writing about our work as therapists. Some guidelines are given in order that phenomenological good practice be maintained.